Forum: (De)centring Europe in urban communication research. Issue 4 (2nd October 2021) - Aiello, Giorgia
ABSTRACT: This special forum includes six contributions by scholars affiliated with the European Communication Research and Education (ECREA) "Media, Cities and Space" Section. It focuses on "European" urban communication research as a way to explore what matters, both critically and theoretically, in media and communication studies of the urban. As a whole, the special forum aims to "decentre" existing assumptions regarding the urban locales, critical questions, and conceptual outlooks covered in each contribution-both from pre-constituted notions of "Europeanness" and from dominant approaches to the relationship between communication, media, and the urban.